Study of Various Morphological Types of Anaemia in Patients With rheumatoid Arthritis and Comparison of Serum Ferritin with Bonemarrow Iron Stores in These Patients. - Dilip M Pancholi; Shyam N Shah; Ketul Joshi (Asian Journal of Medical Research, 2019)
Background: Anemia is a common extra-articular manifestation in rheumatoid arthritis patients. Its severity roughly parallels the activity of the disease1-2. Chronic disease and iron deficiency are considered to be the most significant causes of anemia 3-5. Anemia of chronic disease is usually confused with iron deficiency anemia due to the low level of iron in blood in both forms of anemia. Subjects and Methods:This study was conducted in Department Of Medicine, C. U. Shah Medical College, Gujarat, India. 68 total number of population were included in this study.The duration of study was over a period of six month. Results:In our study, 68 total numbers of cases were included. Among all cases 58.8 % were male & 41.2% were female. In the present study, 41.2% cases were belongs to 31-40 age group followed by 41-50(35.2%), <30 (11.7%) &>50 (11.7%) age group. This study suggested type of anemia which was found 76.5%Normocytic Normochromic followed by Microcytic Hypochromic 23.5%.Conclusion: Therefore, it can be concluded from the present study that normocytic normochromic anemia is the most common morphological type of anemia in patients with rheumatoid arthritis. And there is a positive correlation between serum ferritin and BMIS in RA patients presenting with anemia. The results of this study also revealed that serum ferritin is an useful index of iron stores in rheumatoid arthritis.